DESIGN OF INVERTER FOR HIGH CURRENT INDUCTIVE LOAD APPLICATION - NARENDRAN, LOGANATHAN (IRC, 2019)
DC to AC multilevel inverter is being researched and tested out currently by various institutes for ‘ideal’ approach towards uninterruptable power supply, commonly known as “UPS”. By doing case study, an innovative proposition was brought forward with manufacturing cost and efficiency in mind. This proposed method follows the concept of H-bridge configuration which use lesser components and has lower harmonic rate at output. In detail, the innovative method is made up of certain level which consists capacitors, MOSFETs, diodes and transformer. The limitations are complexity of circuit structure as well as need of precise planning to tackle issue of separate DC sources for every H-bridge cell. There is also heat management of components issue due to production of high current to support 1kW load. Furthermore, sustainability is an issue as continuous 1000-watt power output in sine waveform need to be demonstrated followed by setting limits. The expected outcome is to able produce 1000-Watt output from 12VDC battery through DC to AC conversion. Moreover, the output should be continuously in ‘perfect’ sinusoidal waveform as Sinusoidal Pulse Width Modulation (SPWM) method is utilised which contribute to efficiency by lowering harmonics. The simulation should include staircase wave form which is proof that multilevel inverter is implemented, and that the method was further developed